2013
DOI: 10.1016/j.diabres.2012.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of paraoxonase-1 activity may contribute the qualitative impairment of HDL particles in patients with type 2 diabetes

Abstract: We confirmed the functional changes in HDL particles in the patients. Efflux-hdl from macrophages was reduced depending upon the decrease in PON1 activity, which was inversely related to HbA1c levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
1
18
0
1
Order By: Relevance
“…This was also demonstrated in a study by Khera and colleagues, where patients in secondary prevention (including 23% with T2D) had a reduced cholesterol efflux capacity independent of their HDL levels [36]. In agreement with this finding, recent data by another group showed that HDL particles obtained from T2D patients were characterized by a decreased paraxonase-1 activity, inversely correlated to HbA1c levels [37].…”
Section: Type 2 Diabetes and Dyslipidemiasupporting
confidence: 77%
“…This was also demonstrated in a study by Khera and colleagues, where patients in secondary prevention (including 23% with T2D) had a reduced cholesterol efflux capacity independent of their HDL levels [36]. In agreement with this finding, recent data by another group showed that HDL particles obtained from T2D patients were characterized by a decreased paraxonase-1 activity, inversely correlated to HbA1c levels [37].…”
Section: Type 2 Diabetes and Dyslipidemiasupporting
confidence: 77%
“…Previously, it was shown that enrichment of HDL with SAA decreases its cholesterol efflux properties1840, which also translates into lower in vivo reverse cholesterol transport in a rodent model25. However, it should be noted that in a small-scale study in humans no impact of SAA on THP-1-mediated efflux towards HDL from T2DM patients has also been reported41. On the other hand, SAA has been linked to impairment of other key functions of HDL such as the protection against oxitative stress42 and inflammation43.…”
Section: Discussionmentioning
confidence: 98%
“…PON-1 associates with HDL to prevent its oxidation by copper ions as well as reducing the peroxide and aldehyde content of HDL, this interaction also lessens LDL atherogenic potential, thus potentially reducing the risk of development of atherosclerosis [39]. Previous studies have found PON-1 activity to be lower in those with T2DM [40, 41] implicating the impairment of HDL antioxidant properties. However, when those taking insulin and GLP-1 analogues were excluded, serum-PON-1 activity was more comparable between groups, similar to that observed for PON-1 activity in HDL 2 and HDL 3 , which may result from a lack of change in apoAI concentration that is required for the stabilisation of PON-1 and its association with HDL.…”
Section: Discussionmentioning
confidence: 99%